1994
DOI: 10.1177/016502549401700106
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Memory Span and Measures of Imitative and Spontaneous Language Complexity in Preschool Children

Abstract: Preschool children, aged 2 to 5 years, were given a memory task that required them to repeat a list of animal names and a sentence imitation task. A sample of their spontaneous speech was also recorded. Word span was found to predict sentence imitation scores across the whole preschool age range. Word span and chronological age (CA), together, also predicted the mean length of utterance in spontaneous speech in younger preschool children. In a replication with children aged 2 to 3 years, word span predicted me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 16 publications
5
45
1
3
Order By: Relevance
“…Adams and Gathercole, therefore, concluded that verbal short-term memory predicts syntactic development. Blake, Austin, Cannon, Lisus, and Vaughan (1994) found similar results for children between 2 and 5 years of age. A study by Montgomery (1995) found a strong positive correlation between verbal short-term memory skills and levels of sentence comprehension in a study of 14 children with specific language impairment and 13 typically developing control children.…”
Section: Verbal Short-term Memory and Grammar Developmentsupporting
confidence: 65%
“…Adams and Gathercole, therefore, concluded that verbal short-term memory predicts syntactic development. Blake, Austin, Cannon, Lisus, and Vaughan (1994) found similar results for children between 2 and 5 years of age. A study by Montgomery (1995) found a strong positive correlation between verbal short-term memory skills and levels of sentence comprehension in a study of 14 children with specific language impairment and 13 typically developing control children.…”
Section: Verbal Short-term Memory and Grammar Developmentsupporting
confidence: 65%
“…VSTM shows strong associations with word learning (Gathercole, Willis, Emslie, & Baddeley, 1992; see Gathercole, 2006, for an overview) as well as with the production of long and grammatically complex sentences (Adams & Gathercole, 1996, 2000Blake, Austin, Cannon, Lisus, & Vaughan, 1994). VWM is related to grammar learning, more specifically, to monolingual children's grammaticality judgments (Gottardo, Stanovich, & Siegel, 1996), receptive syntax (Ellis Weismer, Evans, & Hesketh, 1999), and sentence comprehension (Montgomery, 1995).…”
Section: Verbal Working Memory and Language Learningmentioning
confidence: 99%
“…Depuis la discussion de Baddeley, Gathercole et Papagno (1998), les chercheurs considèrent avec plus de sérieux la possibilité que la MP ait un rôle significatif à jouer non seulement dans l'acquisition du vocabulaire (en Ll, voir : Baddeley et al 1998;Gathercole, Hitch, Service & Martin, 1997;en 12, voir : Atkins & Baddeley, 1998;Cheung, 1996), mais aussi dans l'acquisition de la grammaire, et ce, autant en Ll (Adams & Gathercole, 1996;Blake, Austin, Cannon, Lisus & Vaughan, 1994) qu'en L2 (Adams & Gathercole, 1995;Blake et al, 1994) Toutefois, la relation entre la facilité à apprendre du vocabulaire et l'habileté à apprendre et appliquer des règles grammaticales n'est pas confirmée. De plus, tandis que l'apprentissage de vocabulaire nouveau exige l'emmagasinage de formes phonologiques nouvelles ou inconnues, l'apprentissage et la mise en application de règles de grammaire requièrent souvent l'emmagasinage et le traitement de morphèmes apparentés ou connus.…”
Section: Problématiques Générale Et Spécifiqueunclassified